The impact of pre-oxidation with potassium permanganate on cyanobacterial organic matter removal by coagulation - Naceradska, Jana; Pivokonsky, Martin; Pivokonska, Lenka; Baresova, Magdalena; Henderson, Rita K; Zamyadi, Arash; Janda, Vaclav (Water research, 2017)
The study investigates the effect of permanganate pre-oxidation on the coagulation of peptides/proteins of Microcystis aeruginosa which comprise a major proportion of the organic matter during cyanobacterial bloom decay. Four different permanganate dosages (0.1, 0.2, 0.4 and 0.6 mg KMnO4 mg-1 DOC) were applied prior to coagulation by ferric sulphate. Moreover, changes in sample characteristics, such as UV254, DOC content and molecular weight distribution, after pre-oxidation were monitored. The results showed that permanganate pre-oxidation led to a reduction in coagulant dose, increased organic matter removals by coagulation (by 5-12% depending on permanganate dose), microcystin removal (with reductions of 91-96%) and a shift of the optimum pH range from 4.3 to 6 without to 5.5-7.3 with pre-oxidation. Degradation of organic matter into inorganic carbon and adsorption of organic matter onto hydrous MnO2 are suggested as the main processes responsible for coagulation improvement. Moreover, permanganate prevented the formation of Fe-peptide/protein complexes that inhibit coagulation at pH about 6.2 without pre-oxidation. The study showed that carefully optimized dosing of permanganate improves cyanobacterial peptide/protein removal, with the benefit of microcystin elimination.
Keywords: Coagulation; Adsorption; Water treatment; Potassium Permanganate; manganistan draselný; Microcystis aeruginosa; oxidace-redukce; čištění vody; Water Purification; Algal organic matter; Microcystis; Permanganate pre-oxidation; Oxidation-Reduction; adsorpce; Peptides/proteins